Magnesium sulphate for fetal neuroprotection at imminent risk for preterm delivery: a systematic review with meta‐analysis and trial sequential analysis. (17th May 2020) - Wolf, HT; Huusom, LD; Henriksen, TB; Hegaard, HK; Brok, J; Pinborg, A
Abstract : Background: Ordinary meta‐analyses indicate that magnesium sulphate (MgSO4 ) treatment in women at imminent risk for preterm delivery decreases the offspring's risk of cerebral palsy (CP). However, repetitive testing of cumulative data calls for statistical caution, e.g. by trial sequential analysis (TSA), for which there are previously insufficient samples to draw a firm conclusion. Recently, a randomised controlled trial (RCT) provided additional data that potentially increased the sample size such that a new TSA might detect a statistically significant effect. Objectives: To assess the possible fetal neuroprotective effect of MgSO4 for women at imminent risk for preterm delivery in an updated systematic review with meta‐analysis and TSA. Search strategy: We searched MEDLINE, Embase, Cochrane and ClinicalTrials.gov on 8 October 2019. The search strategy clustered terms describing the MgSO4 intervention and preterm delivery. Selection criteria: RCTs. Data collection and analysis: Two reviewers extracted the data. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated using fixed‐effects models. A TSA was applied to the primary outcome, CP. The quality of the evidence was assessed using GRADE. The protocol was registered in PROSPERO (registration: CRD42019151441). Main results: We identified six eligible trials (5917 women). MgSO4 intervention in women at imminent risk for preterm birth decreased the offspring's CP risk (meta‐analysis RR 0.68, 95% CI 0.54–0.85; TSA RR 0.69, 95% CI 0.48–0.97). Conclusions: This systematic review with meta‐analysis and TSA shows conclusively that MgSO4, when given to women at imminent risk for preterm delivery, decreases the offspring's CP risk. Tweetable abstract: Antenatal magnesium sulphate decreases the risk of cerebral palsy in children born preterm. Tweetable abstract: Antenatal magnesium sulphate decreases the risk of cerebral palsy in children born preterm.